SOSIALISASI MENGENAI DIGITALISASI DALAM MEMPERKUAT PARTISIPASI PADA SAAT PEMILU TAHUN 2024 DI DESA PEMECUTAN KAJA BANJAR GRENCENG - Kadek Adyatna Wedananta; Amalia Zhahrotul Havida; I Gst. Ayu P. Jesika Sita Devi N (LP2M STP Mataram, 2024)
Digitalization has become an integral part of people's lives, including the democratic process. The use of digital technology in elections can be an effective tool for increasing voter participation, especially among the younger generation. Digitalization can increase voter participation in several aspects, including, Information and Education as a digital platform that can be used to disseminate information and education about elections to the wider community, especially the younger generation, Voter Registration where the voter registration process can be made easier and accessed online, thus increasing voter participation, Socialization and Campaigns to conduct political campaigns can be carried out online through social media and other digital platforms, thereby reaching more voters, and Monitoring and Supervision Digital platforms can be used to monitor and supervise the course of elections, thereby increasing transparency and accountability